Empowerment of Productive Youth Group Asset-Based In The Business of Establishing a Collective Business In Talunkenas Village, STM Hilir District Deli Serdang Regency - Nurman Achmad; Hatta Ridho; Husni Thamrin (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
Youth is the nation's asset, determining the future direction of a better life. Their existence becomes a renewing energy and is critical of a distorted establishment. Youth is the breath of the times, the ideal group of the ummah and the nation who are rich in criticism, imagination, and their role in every event that occurs in the midst of changing society. It is undeniable that youth play an important role in almost every social transformation and struggle to achieve goals. The success of youth development as quality human resources with competitive advantage is one of the keys to opening opportunities for success in various other development sectors. Therefore, youth empowerment is considered as one of the programs that cannot be ignored in preparing the nation's life in the future. Youth have valuable assets as capital to make changes. These assets must be utilized so that they can be useful. Youth empowerment can be done through various ways, both in formal, informal, and non-formal channels. The purpose of empowerment is basically to shape the character of youth, so that they become fully Indonesian human beings or humans who have character that can optimize the talents or assets of youth so that they can prosper individuals and groups. Partners in community service with this Community Partnership Program scheme are the Talun Kenas Village Government, STM Hilir District, Deli Serdang Regency, North Sumatra Province. The output targets of this program are scientific publications, mass media publications, activity videos and being speakers in scientific meetings. The method used in this program is program socialization and Participatory Learning and Action (PLA) involving all targets so that young people can be empowered by releasing all their assets to form a joint business for mutual benefit.